Job finding web application for computer science graduate / Muhammad Afiq Firdaus Fadzil - Fadzil, Muhammad Afiq Firdaus (2020)
Nowadays there are already many job portal web applications available in the World Wide Web such as Job Street, MauKerja and Monster. In each of this web applications, they cover all types of job in every industry to offer for user from agriculture, healthcare, banking and creative arts. When this happen, it will be hard to navigate the website to find the job that user wanted. They will find the job but it will take some time to accustomed to the website design and interface with all the different jobs that they are offering randomly. To solve this problem, Job Access web application will be developed where it focuses on computer science industry. All type of jobs vacant that involve computer science can be publish and promote here. Job for computer science major cannot be underestimated because there are many requirements of skills and expert in any software that is needed for the job. Job Access web application will display all of it and making sure Computer Science graduate from any University and any people that have the computer skills find their suitable job here and making Job Access their first choice of Computer Science Web Application Job Portal.